Sistem Informasi Pengarsipan Dokumen ISO Berbasis Website di PT. Hikari Teknologi Indonesia - Wahyu Hidayat; Henny Dwi Bhakti (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
PT. Hikari Teknologi Indonesia has implemented an information system covering human resources, finance, operations and marketing that can support and accelerate internal activity data information. However, there are problems with the document data system which still uses a manual system. This means that the document process is still in physical form. In addition, the efficiency of document data is still low and the accuracy of searching document report data is still low, making it difficult and not automated for HRGA department staff in managing document data management during modernization. With this system, it is very helpful for the HRGA department in supporting the storage activities of the company PT. Hikari Teknologi Indonesia. The filing system makes it easy to generate reports and upload documents.